Internalization of Tasawuf Values in Learning Fiqh at Madrasah Aliyah Sambas Kalimantan - Suriadi Suriadi (Jurnal Pendidikan Islam, 2018)
This study was aimed in order to uncover and discover the efforts of teachers in internalizing the values of Sufism in learning Fiqh in MAN (Madrasah Aliyah Negeri/ State Islamic Senior High School) Sambas Regency, West Kalimantan Province. This research was conducted using qualitative descriptive analytic approach. Meanwhile, to collect the necessary data used in this study in-depth interview techniques, observation, and documentation study. This study led to the conclusion: the techniques used by teachers to internalize the values of Sufism in learning Fiqh is to link subject matter of Fiqh with the values of Sufism, reveal hikmat at-tasyri’, assignment, and imitation, factors that support the internalization of the values of Sufism in learning Fiqh are the internal factors of teachers that includes knowledge and insights, learning strategies, learning facilities such as mosques, dormitories and libraries, and constraints faced by teachers are class size, social environment, and the influence of the mass media.